Tatawwur al-Wasāil al-Sam’iyyah wa al-Baṣariyyah fī Ta'līm Mahārah al-Istimā’ bi al-Ma’had - Busro, Muh; Astuti, Dwi Erviana; Putra, Wahyu Hanafi (Study Program of Arabic Language Teaching, 2025)
The purpose of this study is to describe the development of audio-visual learning media for istimā’ (Arabic Listening Skills) instruction at Pondok Modern Arrisalah, International Program, Ponorogo. This study employs a qualitative approach using a case study design. The research data consist of activities related to the implementation and development of audio-visual learning media during istimā’ instruction in Class IV D of KMI (Kuliyyāt al-Mu’allimīn wa al-Mu’allimāt al-Islāmiyyah). Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that: (1) the learning media used in Arabic language instruction in Class IV D of KMI include audio media, visual media, audio-visual media, as well as printed media sourced from textbooks and dictionaries; (2) the use of audio and visual media provides many benefits for students, including facilitating their understanding of lessons. Arabic learning materials delivered through audio-visual media are more strongly retained and more focused in students’ memory, and they help reduce boredom during the learning process; and (3) prior to implementing audio-visual media in instruction, teachers prepare by referring to learning objectives, identifying students’ abilities, preparing learning materials, ensuring the availability of facilities and infrastructure, mastering appropriate teaching methods, using learning media effectively, and conducting evaluations.